The Racialization of Food: “Indian Corn”, Disgust, and the Development of Underdevelopment in Depression-Era British Honduras - Christine A. Kray (Humans)
This paper explores the co-constitution of systems of social distinction, culinary habits, and political economies. During the Depression in British Honduras (Belize), unemployment, hunger, and malnutrition ignited panic, unrest, and uprising. At the same time, agents of a mahogany company and the colonial government displaced an entire Maya farming community. Why was Maya farming not considered a pillar of the colony’s economy? For more than a century, colonial administrators had made scarce attempts to stimulate domestic food production and distribution, and stimulating corn production was not even considered. Corn had become racialized, called “Indian corn”, and was considered disgusting, unhealthy, and the cause of high Indian mortality rates. A visceral disgust for corn was hard to disentangle from British disgust for Indians more generally. The racialization of corn emerged alongside and reinforced colonial economic policies of structural underdevelopment, all of which ensured that when Belize City residents were standing in food lines, the abundant harvests of Indian corn were nowhere within reach.